Integration of Community Nursing in Family Empowerment Programs to Improve Adolescent Reproductive Health - Herlina Lidiyawati (Journal of Public Health Indonesian, 2025)
This study aims to develop and test the effectiveness of integrating community nursing into a family empowerment program to improve adolescent reproductive health. The research background is based on the high prevalence of adolescent reproductive health problems in Indonesia, such as early marriage, unwanted pregnancy, and sexually transmitted infections, which are exacerbated by poor family communication regarding these topics. The study used a Participatory Action Research (PAR) approach involving adolescents aged 12–19 years, their families, and community nurses in the community health center (Puskesmas) working area. The research instruments included an in-depth interview guide, a participant observation sheet, and pre- and post-test questionnaires on knowledge and attitudes. The results showed a significant increase in adolescent knowledge, attitudes, and healthy behaviors (p < 0.05) after the intervention, accompanied by an increase in the frequency of open communication between families and adolescents regarding reproductive health. The involvement of families as co-educators has been shown to strengthen the program's effectiveness, create a supportive home environment, and reduce cultural barriers in discussing reproductive issues. This intervention model is considered to have great potential for replication in various regions with adjustments to the local social and cultural context, thus becoming a sustainable strategy in promoting adolescent reproductive health.